1980
DOI: 10.1246/bcsj.53.1902
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of 2-Hydroxy Acids by Copper(II) Species in Aqueous Solution

Abstract: Ultraviolet irradiation of aqueous lactic, glycolic, or 2-hydroxybutanoic acid in the presence of copper(II) leads to photoredox reaction to give corresponding α-keto acid, aldehyde with evolution of carbon dioxide, and the precipitate of copper(I). The mole ratio of the carbonyl products to the consumption of copper(II) is close to 0.5. Oxidative decarboxylation dominates at pH>1 while the formation of α-keto acids favors at lower pH. The formation of α-keto acids is selectively suppressed by the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The decarboxylation of carboxylic acids under UV light irradiation in presence of Cu(II) salts has been known for 50 years, [77][78][79][80][81] but it was not until 2021 when the first synthetic methodologies exploiting this reactivity emerged. Interestingly, while decarboxylation of aliphatic carboxylic acids via LMCT irradiation was attained before employing Fe(III) [82] or Ce(IV) [83] catalysts, the considerably more challenging decarboxylation of aryl carboxylic acids was first unveiled by Ritter and coworkers, who reported a method for the decarboxylative fluorination aryl carboxylic acids using stoichiometric copper and fluoride salts (Scheme 7).…”
Section: Reactions Mediated By Cu(ii) Complexesmentioning
confidence: 99%
“…The decarboxylation of carboxylic acids under UV light irradiation in presence of Cu(II) salts has been known for 50 years, [77][78][79][80][81] but it was not until 2021 when the first synthetic methodologies exploiting this reactivity emerged. Interestingly, while decarboxylation of aliphatic carboxylic acids via LMCT irradiation was attained before employing Fe(III) [82] or Ce(IV) [83] catalysts, the considerably more challenging decarboxylation of aryl carboxylic acids was first unveiled by Ritter and coworkers, who reported a method for the decarboxylative fluorination aryl carboxylic acids using stoichiometric copper and fluoride salts (Scheme 7).…”
Section: Reactions Mediated By Cu(ii) Complexesmentioning
confidence: 99%
“…46 Fe(IV) porphyrins have been catalytically regenerated with peroxy acids. 47 Matsushima et al 48 reported that the photolytic decarboxylation of Cu(II) lactate yielded acetaldehyde and pyruvate. They also showed that pyruvate resulted from the formation of radical species, and that the addition of radical traps reduced the formation of pyruvate to almost zero.…”
Section: Photochemical Hofer-moest Reactionsmentioning
confidence: 99%
“…24 The C-H bond energy is smaller in chloroform than it is in dichloromethane, 25 which might explain why the hydroperoxide accumulates in irradiated chloroform. 26 Several photoreactions of copper(II) complexes in organic solvents are known in which reduction to copper(I) occurs, [27][28][29][30][31] including several studies of copper(II) chloride and chlorocuprate(II) complexes. 23,[32][33][34][35][36][37] If the chlorocuprate(I) product from the photolysis of CuCl 4 2in a halocarbon could be reoxidized to copper(II), as occurs with iron(II/III), the net result of an oxidation-reduction cycle would be the degradation of the halocarbon.…”
Section: Introductionmentioning
confidence: 99%
“…Several photoreactions of copper(II) complexes in organic solvents are known in which reduction to copper(I) occurs, including several studies of copper(II) chloride and chlorocuprate(II) complexes. , If the chlorocuprate(I) product from the photolysis of CuCl 4 2− in a halocarbon could be reoxidized to copper(II), as occurs with iron(II/III), the net result of an oxidation−reduction cycle would be the degradation of the halocarbon. We undertook an investigation of this process in dichloromethane, with the assumption that absorption into the ligand-to-metal charge transfer (LMCT) bands of CuCl 4 2− , which extend from the UV into the blue part of the spectrum, , would cause chlorine atom dissociation, initiating the decomposition process (eq ).…”
Section: Introductionmentioning
confidence: 99%